Second language acquisition theory the legacy of professor Michael H. Long - Long, Michael H.; Benati, Alessandro G.; Schwieter, John W., 1979- (Bilingual processing and acquisition ;, 2022)
"Professor Michael H. Long (1945-2021) was one of the most influential scholars in the field of second language acquisition. This volume presents a set of chapters that honour some of his key contributions in language teaching and learning. Following a bibliometric analysis of the impact of his research to the field, the volume spans topics such as task-based language teaching, focus on form, age effects, transfer, feedback, interaction, incidental learning, stabilization, among many others"--